(untitled) (CAHIERS MAGELLANES-NS, 2024)
Introduction: Disasters can overwhelm community resources and response capabilities, necessitating external support. Effective disaster preparedness is crucial for healthcare professionals. Robust disaster management strategies, as emphasized by the Sendai Framework, enhance hospital readiness. Nepal's 2015 earthquake and COVID-19 highlighted the need for improved emergency management, leading to the establishment of Health Emergency Operation Centers (HEOC) and a network of hospitals. However, ongoing challenges like resource shortages and coordination issues highlight the need for enhanced disaster preparedness. Materials and Method: A comprehensive literature review was conducted to address gaps in Nepal's emergency and disaster preparedness research. Using search strategies across databases, the review aimed to map significant ideas and evidence in a complex and under-researched topic. The review focused on articles published from 2019 to 2024 to evaluate the effectiveness of current strategies and identify areas for improvement in Nepal's disaster preparedness and response systems. Results: Prior disasters and emergencies exposed Nepal's healthcare system's weaknesses, including worker hesitancy, resource shortages, and logistical inefficiencies. Challenges like delayed case detection and inadequate surveillance worsened the crisis. Despite the presence of Hospital Emergency Operation Center (HEOC), Hospital Emergency Incident Command System (HEICS) & satellite hospitals, the gaps regarding disaster emergencies still persisted. The study found major gaps in emergency plans, including poor infrastructure and communication systems. Conclusion: The pandemic has highlighted the need for a comprehensive approach to address gaps in healthcare. This includes improving hospital preparedness, establishing surge capacity plans, and enhancing community engagement. Effective disaster management requires developing emergency plans, robust communication systems, and addressing human resources and logistics deficiencies